Preparation method of kilogram-level SBA-15 with controllable specific surface
By synthesizing SBA-15 materials at different temperatures, using P123 and tetraethyl silicate, the problems of SBA-15 materials in large-scale mass production and structural stability were solved, and the kilogram level was controlled and improved. Its performance and scope of use in multiple application areas.
Patent Information
- Application Number
- CN202411366630.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-20
AI Technical Summary
The existing SBA-15 materials are difficult to reach the kilogram level in large-scale mass production, and the high specific surface area causes the material to easily break under external forces, and the structural stability is insufficient, which limits its performance and scope of use in actual applications.
Polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (P123) is used as the template agent and tetraethyl silicate is used as the silicon source to synthesize kilogram-level ordered pores and ratios under weak acidic environments at different temperatures. The adjustable SBA-15 material is used to control the specific surface area of the material by controlling the reaction speed and crystallization temperature.
Mass production of kilogram-level SBA-15 has been achieved, and the structural stability and application diversity of materials have been improved by controlling the specific surface area. It is suitable for catalysis, adsorption separation, drug transmission and battery fields.
Smart Images

Figure CN119160909A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of mesoporous materials, and relates to a method for preparing SBA-15, and in particular to a method for preparing kilogram-level specific surface controllable SBA-15. Background Art
[0002] Mesoporous materials have the characteristics of large specific surface area, large pore volume, uniform nanoscale pore size, and ordered pore structure from one dimension to multiple dimensions. SBA-15 material is one of the representative materials of ordered mesoporous silicon-based molecular sieves. SBA-15 mesoporous molecular sieves can be synthesized in a strong acid environment. SBA-15 mesoporous molecular sieves have the characteristics of high specific surface area, ordered pore structure, and large volume. The synthesis conditions of SBA-15 are relatively mild. Because the surfactant is easy to remove, it is not easy to cause structural collapse. The repulsion between neutral surfactants and neutral inorganic precursors is much smaller than the repulsion between charged inorganic precursors and charged inorganic precursors, so that thicker pore walls can be formed, and the thermal stability and hydrothermal stability of the molecular sieve skeleton structure can be improved. The characteristics of SBA-15 materials make it have good application prospects in the fields of macromolecular adsorption and separation, chemical sensors, biomedicine, chemical catalysis, environmental protection and nanomaterial synthesis.
[0003] Although SBA-15 has good applications in various fields, at present, most of the reported syntheses of SBA-15 cannot achieve large-scale mass production, and are all at the gram level, and cannot reach the level of kilograms or even several kilograms. At the same time, the specific surface area is particularly critical for the application of SBA-15 in different fields. SBA-15 with high specific surface area can load a large number of drug molecules to achieve sustained and controlled release of drugs. The ordered mesoporous structure can protect drug molecules from the influence of the external environment and improve the stability of drugs. However, high specific surface area is usually accompanied by thinner pore walls and more complex pore structures. This makes the material more prone to rupture or collapse when subjected to external forces, such as pressure, friction, etc. In practical applications, such as during the loading and use of catalysts, the material may be subjected to fluid impact and pressure changes, and insufficient mechanical strength may lead to material breakage and performance degradation. Therefore, SBA-15 with different specific surface areas has many advantages, but it is not the so-called bigger the better. In practical applications, it is necessary to comprehensively consider factors such as specific surface area, structural stability, and adsorption selectivity according to specific needs and application scenarios. In order to solve the technical problems existing in the background technology, this paper uses polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (P123) as a template and tetraethyl silicate as a silicon source to synthesize kilogram-level mesoporous material SBA-15 with ordered pores and adjustable specific surface area in a weakly acidic environment at different temperatures. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing kilogram-level SBA-15 with controllable specific surface area.
[0005] Technical solution: In order to achieve the above purpose, the present invention provides a method for preparing kilogram-level specific surface controllable SBA-15, comprising the following steps:
[0006] (1) Add P123 to aqueous hydrochloric acid in a large reactor at 35-42°C and stir to obtain a transparent solution;
[0007] (2) adding tetraethyl orthosilicate dropwise to the transparent solution obtained in step (1), and continuing stirring at 35-42° C. for 20-30 hours to obtain a milky white solution; the total time for adding tetraethyl orthosilicate dropwise is 3 hours, wherein the rotation speed is 90 rpm within 0 to 1.5 hours of adding, and 120 rpm within 1.5 to 3 hours of adding, and immediately changing to 90 rpm after the addition is completed for 3 hours;
[0008] (3) The milky white solution is transferred into a reactor, sealed, crystallized at 100-140° C. for 24-48 hours, centrifuged, washed, dried, and then ground into powder to obtain kilogram-level SBA-15 with controllable specific surface.
[0009] Wherein, P123 in step (1) is preheated in an oven at 60° C. for 4 to 8 hours before being added to the reactor.
[0010] Wherein, the mass ratio of P123 to the aqueous hydrochloric acid solution described in step (1) is (0.15-0.2):1, and the concentration of the aqueous hydrochloric acid solution is 1.5 mol / L-2.5 mol / L.
[0011] Wherein, the mass ratio of the ethyl orthosilicate solution in step (2) to the P123 in step (1) is (2-2.5):1.
[0012] Wherein, in step (2), ethyl orthosilicate is evenly distributed into a plurality of dropping bottles, and the plurality of dropping bottles are dripped at the same time, and the droplet speed of the dropping bottles is adjusted so that the droplets flow in evenly but do not form a line.
[0013] The centrifugation, washing and drying steps in step (3) are as follows: after the solution is crystallized, after the solution is cooled to room temperature below 25°C, the solution is transferred to a large-scale spin dryer for washing 3 to 4 times; the large spin dryer is adjusted to a speed of 1000 to 2000 rpm for centrifugation for 20 to 30 minutes, 10 to 15 L of deionized water is added, mixed evenly, the speed is adjusted to 2000 to 3000 rpm for centrifugation for 20 to 30 minutes, 10 to 15 L of deionized water is added again, mixed evenly, and the speed is adjusted to 3000 to 4000 rpm until all the deionized water is washed clean; the washed product is transferred to a crucible, placed in an oven, the oven temperature is set to 60 to 80°C for drying, and naturally cooled to room temperature.
[0014] Among them, the step of grinding into powder in step (3) is: grinding the dried product with a stainless steel powder grinder for 20 seconds, setting the speed to 10,000 rpm to grind into powder, and the obtained white product is kilogram-level SBA-15 powder.
[0015] Wherein, when the crystallization temperature in step (3) is 100°C, the specific surface area of the SBA-15 is 800m 2 / g.
[0016] Wherein, when the crystallization temperature in step (3) is 120°C, the specific surface area of the SBA-15 is 600m 2 / g.
[0017] Wherein, when the crystallization temperature in step (3) is 140°C, the specific surface area of the SBA-15 is 400 m 2 / g
[0018] Reaction mechanism of the present invention: The present invention can obtain mass production of kilogram-level SBA-15 by performing dropwise reaction at a specific reaction speed of 90 rpm and a mixed speed of 120 rpm, and at the same time obtain SBA-15 with a desired specific surface area by setting different crystallization temperatures. When the crystallization temperature is set to 100°C, 800 m 2 When the crystallization temperature is 120℃, 600m 2 When the crystallization temperature is set to 140 °C, 400 m 2 / g specific surface area; the reason is that with the increase of crystallization temperature, the hydrophobicity of the EO block in the surfactant increases and the hydrophilicity decreases, so the length of the EO block interacting with the silicon wall decreases, which leads to an increase in the hydrophobic volume of the surfactant aggregates and an increase in the pore size of SBA-15. As the pore size increases, the specific surface area decreases; in addition, with the increase of temperature, the hydrolysis and polycondensation reactions of silicon species are strengthened, the surface charge density of inorganic silicon species increases, and the interfacial bending energy decreases, which is conducive to the formation of curved products, so that the rope-like aggregates gradually open, and the original series of donut sticks begin to scatter, forming scattered "banana"-shaped short sticks, and the scattered short sticks gradually become thinner and longer with the increase of crystallization temperature, resulting in a decrease in the specific surface area. Therefore, by adjusting the crystallization temperature, SBA-15 with controllable specific surface area can be further obtained.
[0019] Beneficial effects: Compared with the prior art, the advantages of the present invention are: the present invention provides a method for preparing kilogram-level SBA-15 with controllable specific surface area, the method realizes the mass production of kilogram-level SBA-15, and realizes the controllability of specific surface area by controlling the conditions of hydrothermal crystallization. SBA-15 with different specific surface areas has important applications in the fields of catalysis, adsorption separation, drug delivery and batteries. The present invention gives full play to the large-scale production and various applications of SBA-15 with different specific surface areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 a is the specific surface area of 800 m2 prepared in Example 1 at a reaction speed of 90 rpm, a mixed speed of 120 rpm and a crystallization temperature of 100°C. 2 / g SBA-15 XRD pattern, Figure 1 b is its TEM characterization;
[0021] Figure 2 a is the specific surface area of 600 m2 prepared in Example 2 at a reaction speed of 90 rpm, a mixed speed of 120 rpm and a crystallization temperature of 120°C. 2 / g SAB-15 XRD pattern, Figure 2 b is its TEM characterization;
[0022] Figure 3 a is the specific surface area of 400 m2 prepared in Example 3 when the reaction speed is 90 rpm, the mixed speed is 120 rpm and the crystallization temperature is set to 140°C 2 / g SAB-15 XRD pattern, Figure 3 b is its TEM characterization.
[0023] Figure 4 a is the XRD spectrum of SBA-15 prepared at a reaction speed of 90 rpm in comparative example 1, Figure 4b is its TEM characterization;
[0024] Figure 5 a is the XRD spectrum of SBA-15 prepared at a reaction speed of 120 rpm in Example 2, Figure 5 b is its TEM characterization. DETAILED DESCRIPTION
[0025] Example 1 Preparation of Kg-Grade Specific Scale Controlled SBA-15
[0026] 1. Add 39.75 kg of deionized water to a 100 L large reactor; then add 6.65 kg of 14 mol / L concentrated hydrochloric acid to the large reactor; preheat the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (P123 template) (Aladdin P434427) in an oven at 60 ° C, then add 1.3 kg of preheated P123 template to the reactor, turn on the stirring equipment, set the temperature to 42 ° C, turn on the circulating water, stir at a speed of 90 rpm, and stir for 24 hours until the solution becomes transparent and clear.
[0027] 2. Put 2.765kg of tetraethyl orthosilicate solution into 4 1L dropping bottles respectively, and evenly distribute the same weight; add tetraethyl orthosilicate to the solution obtained in step 1 at the same time, and adjust the speed of the droplets so that the droplets are not connected into a line. It cannot be added too fast or too slowly. Too fast a droplet acceleration will cause tetraethyl silicate lumps, but it cannot be too slow, otherwise the reaction will be incomplete. The speed is 90rpm during dropwise addition, and the dripping is completed in about 3 hours. When the dripping is halfway through in 1.5 hours, the speed is changed to 120rpm. After dripping for 3 hours, it is immediately changed to 90rpm. There should be no surging situation throughout the whole process.
[0028] 3. After 24 hours of reaction, collect the product in a glass bottle, cover the bottle cap, and let it stand until stratification occurs in the barrel. Let it stand for 24 hours, pour out part of the upper clear liquid, set the oven temperature to 100°C, and crystallize for 24 hours. After the crystallization is completed, after the solution is cooled to room temperature below 25°C, the solution is transferred to a large spin dryer for washing 4 times; the large spin dryer is adjusted to a speed of 1000rpm for centrifugation for 20 minutes, 10L of deionized water is added, mixed evenly, the speed is adjusted to 2000rpm for centrifugation for 20 minutes, 10L of deionized water is added again, mixed evenly, and the speed is adjusted to 3000rpm until all the deionized water is cleaned; the cleaned product is transferred to a crucible, placed in an oven, the oven temperature is set to 80°C, dried for 24 hours, and naturally cooled to room temperature; the dried product is ground with a 3L specification 304 stainless steel powder grinder for 20 seconds, the speed is set to 10,000 rpm to grind into powder, and the white product obtained after all grinding is completed is the kilogram-level SBA-15 powder, and the final weighing of all the grinding powder yield is 0.85 kg.
[0029] The obtained powder was subjected to transmission electron microscopy (TEM), X-ray diffraction (XRD) and specific surface area tests. The specific surface area was 800m 2 / g, such as Figure 1 The XRD spectrum shown in a is the specific surface area of 800m 2 / gSBA-15's XRD spectrum. According to the analysis of the legend, it can be found that the position of its characteristic diffraction peak is consistent with the three diffraction peaks of hexagonal mesoporous silica SBA-15, indicating that two-dimensional hexagonal ordered SBA-15 can be obtained within the crystallization temperature range of 100°C, among which the strong diffraction peak near 2θ=0.9° corresponds to the (100) plane, and there are two weaker diffraction peaks between 1° and 2°. Figure 1 b is the specific surface area of 800m 2 / g SM photo shows that when the crystallization temperature is 100℃, the particle shape of mesoporous SBA-15 is donut-shaped. When magnified, it is shown that it is composed of many donuts with a diameter of about 1 micron connected in series into a one-dimensional "long rope".
[0030] Example 2
[0031] The specific steps of this embodiment are basically the same as those of Embodiment 1, except that in step 3, the oven temperature is set to 120° C., and the final output of all the grinding powder is weighed to be 0.9 kg.
[0032] We measured that when the crystallization temperature was 120°C, the specific surface area was 600m 2 / g, Figure 2 a is the XRD pattern of SBA-15, according to Figure 2 The analysis shows that the position of its characteristic diffraction peaks is consistent with the three diffraction peaks of hexagonal mesoporous silica SBA-15, indicating that a crystallization temperature of 120°C can obtain a specific surface area of 600 m 2 / g of two-dimensional hexagonal ordered SBA-15, where the strong diffraction peak near 2θ=0.9° corresponds to the (100) plane, and two weaker diffraction peaks appear between 1° and 2°. Figure 2 b is the specific surface area 600m 2 The TEM image of SBA-15 with a crystallization temperature of 120°C shows that the morphology of SBA-15 is mainly short rods.
[0033] Example 3
[0034] The specific steps of this embodiment are basically the same as those of Embodiment 1, except that in step 3, the oven temperature is set to 140° C., and the final output of all the grinding powder is weighed to be 0.92 kg.
[0035] We measured that when the crystallization temperature was 140°C, the specific surface area was 400m 2 / g, similarly, the specific surface area of the present invention is 400m 2 / g SBA-15 powder was subjected to transmission electron microscopy XRD pattern. Figure 3 It can be found from the analysis that the position of its characteristic diffraction peaks coincides with the three diffraction peaks of hexagonal mesoporous silica SBA-15, indicating that a specific surface area of 400m2 can be obtained within the crystallization temperature range of 140°C. 2 / g of two-dimensional hexagonal ordered SBA-15, where the strong diffraction peak near 2θ=0.9° corresponds to the (100) plane, and two weaker diffraction peaks appear between 1° and 2°. Figure 3 b is the specific surface area 400m 2 / g of SBA-15, we can see scattered "banana"-shaped short sticks of SBA-15.
[0036] Comparative Example 1
[0037] This comparative example is basically the same as Example 1, except that the rotation speed during the dripping in step 2 is 90 rpm and the dripping is completed in about 3 hours. Step 3 is also the same as Example 1, but the final yield is 0.81 kg.
[0038] In order to deeply analyze the change mechanism of the specific surface area of SBA-15, the present invention conducted transmission electron microscopy (TEM), X-ray diffraction (XRD) and specific surface area tests on the obtained powder. 2 / g, such as Figure 4 a shows the XRD pattern, according to Figure 4 Analysis shows that there are no diffraction peaks in the entire spectrum, among which the strong diffraction peak near 2θ = 0.9° corresponds to the (100) plane, and there is no diffraction peak between 1° and 2° that can characterize mesoporous materials. Figure 4 The TEM photo of b shows that the entire morphology is a block or agglomerated reactant, and no ordered mesoporous structure is seen. The reason may be that the stirring speed is too slow, resulting in the inability of the raw material tetraethyl silicate to react effectively with P123 and agglomerate together. Similarly, even if we adjust the experimental speed at 100rpm or 110rpm respectively, the test results are the same as Figure 4 Consistent.
[0039] Comparative Example 2
[0040] This comparative example is basically the same as Example 1, except that the rotation speed during the dripping in step 2 is 120 rpm, and the dripping is completed in about 3 hours. Step 3 is also the same as Example 1, but the final yield is 0.85 kg.
[0041] Similarly, we conducted transmission electron microscopy (TEM), X-ray diffraction (XRD) and specific surface area tests on the obtained powder. The specific surface area was 800m 2 / g, such as Figure 5 a shows the XRD pattern, according to Figure 5 Analysis shows that a tiny diffraction peak appears at 0°~1° in the entire spectrum, indicating that tetraethyl silicate has participated in the reaction and formed a silicon-based material. However, no two diffraction peaks appear between 1° and 2°, indicating that no ordered mesoporous structure appears. Figure 5 In the TEM photo of b, although there are no lumps or agglomerated reactants in the entire morphology, the product of the entire morphology is scattered or broken, and only a small part has formed an orderly pore structure. The reason may be that the stirring speed is too fast, resulting in the raw material tetraethyl silicate being unable to react effectively with P123 and being broken into pieces, and unable to continuously form an orderly pore structure.
Claims
1. A method for preparing kilogram-level SBA-15 with controllable specific surface area. It is characterized in that The following steps are involved: (1) Add P123 to aqueous hydrochloric acid in a large reactor at 35-42°C and stir to obtain a transparent solution; (2) adding tetraethyl orthosilicate dropwise to the transparent solution obtained in step (1), and continuing stirring at 35-42° C. for 20-30 hours to obtain a milky white solution; the total time for adding tetraethyl orthosilicate dropwise is 3 hours, wherein the rotation speed is 90 rpm within 0-1.5 hours of adding, and 120 rpm within 1.5-3 hours of adding, and immediately changing to 90 rpm after the addition is completed for 3 hours; (3) The milky white solution is transferred into a reactor, sealed, and crystallized at 100-140°C for 24-48 hours, centrifuged, washed, and dried, and then ground into powder to obtain SBA-15 with controllable specific surface area at the kilogram level.
2. The method for preparing kilogram-level controllable SBA-15 according to claim 1, It is characterized in that Before adding P123 in step (1) into the reactor, it is preheated in an oven at 60°C for 4 to 8 hours.
3. The method for preparing kilogram-level controllable SBA-15 according to claim 1, It is characterized in that The mass ratio of P123 to the aqueous hydrochloric acid solution in step (1) is (0.15-0.2):1, and the concentration of the aqueous hydrochloric acid solution is 1.5 mol / L-2.5 mol / L.
4. The method for preparing kilogram-level specific surface controllable SBA-15 according to claim 1, It is characterized in that The mass ratio of the ethyl orthosilicate solution in step (2) to the P123 in step (1) is (2-2.5):
1.
5. The method for preparing kilogram-level controllable SBA-15 according to claim 1, It is characterized in that In step (2), ethyl orthosilicate is evenly distributed into a plurality of dropping bottles, and the plurality of dropping bottles are dripped at the same time, and the droplet speed of the dropping bottles is adjusted so that the droplets flow in evenly but do not form a line.
6. The method for preparing kilogram-level specific surface controllable SBA-15 according to claim 1, It is characterized in that The centrifugation, washing and drying steps in step (3) are as follows: after the solution is crystallized, after the solution is cooled to room temperature below 25°C, the solution is transferred to a large spin dryer for washing 3 to 4 times; the spin dryer is adjusted to a speed of 1000 to 1500 rpm for centrifugation for 20 to 30 minutes, 10 to 15 L of deionized water is added, mixed evenly, the speed is adjusted to 2000 to 3000 rpm for centrifugation for 20 to 30 minutes, 10 to 15 L of deionized water is added again, mixed evenly, and the speed is adjusted to 3000 to 4000 rpm until all the deionized water is washed away; the washed product is transferred to a crucible, placed in an oven, and the oven temperature is set to 60 to 80°C for drying, and naturally cooled to room temperature.
7. The method for preparing kilogram-level specific surface controllable SBA-15 according to claim 1, It is characterized in that The step of grinding into powder in step (3) is as follows: grinding the dried product with a stainless steel powder grinder for 20 seconds, setting the rotation speed to 10,000 rpm to grind into powder, and the obtained white product is kilogram-level SBA-15 powder.
8. The method for preparing kilogram-level controllable SBA-15 according to claim 1, It is characterized in that When the crystallization temperature in step (3) is 100 °C, the specific surface area of the SBA-15 is 800 m 2 / g.
9. The method for preparing kilogram-level specific surface controllable SBA-15 according to claim 1, It is characterized in that When the crystallization temperature in step (3) is 120°C, the specific surface area of the SBA-15 is 600 m 2 / g.
10. The method for preparing kilogram-level specific surface controllable SBA-15 according to claim 1, It is characterized in that When the crystallization temperature in step (3) is 140°C, the specific surface area of the SBA-15 is 400 m 2 / g.
